REFLEKSI TIGA BELAS TAHUN PEJUANG BURUH PEREMPUAN ( Kasus Tragedi Marsinah ) - Musfirotun Yusuf (UIN K.H. Abdurrahman Wahid Pekalongan, 2011)
Abstract: Throughout history there, working women have always suffered discrimination and injustice. Wage policy that has not been impartial, social security, welfare to the layoffs, everything is still attached to women workers than male workers. Despite the struggles of women workers already in the beginning since 1872, but has not hasilnyapun memnerikan perbbaikan a significant impact on the fate of the workers especially women workers. Marsinah case is a real reality that should be made ​​an example, both about perseverance, courage and sacrifice in fighting for the rights of workers.